The Relationship between the Head of the Lithuanian Diplomatic Service, Stasys Lozoraitis, and the Supreme Committee for the Liberation of Lithuania between 1950 and 1955 - Jonušauskas, Laurynas (Genocidas ir rezistencija, 2001)
The relationship between Stasys Lozoraitis, the head of the Lithuanian diplomatic service, and the Supreme Committee for the Liberation of Lithuania (VLIK) in the first half of the 1950s can be defined as a continuation of the relations and the non-constructive political dialogue of the previous decade.At consultations in Rome, Nice and Reutlingen in 1950 and 1951, the VLIK sought to subordinate the Lithuanian diplomatic service, while Lozoraitis demanded that the VLIK admit it did not carry out the functions of a Seimas (parliament), and its Executive Council was not a government. No modus vivendi was reached between them.In 1950 Lozoraitis and Alexander Kibbins, an English secret service official, formed a conspiratorial Lithuanian resistance foreign service called Dubysa. It was founded by mutual consent and controlled and financed by the British Secret Intelligence Service.The aim of Western intelligence was to gather information about the situation behind the Iron Curtain and expand their intelligence network. The Lithuanian side hoped that aid from the West would help strengthen the resistance movement in Lithuania.In 1950 the Lithuanian Resistance Concord (LRS) was founded, which acted as a political and psychological shield for Dubysa, and as a sort of protective shield for Lozoraitis against the VLIK.The secret services of Great Britain and the US were concerned about the relationship between Lozoraitis and the VLIK.Meetings of political figures held in Paris and Reutlingen in 1952 demonstrated some willingness to harmonize political activities, but soon relations were dampened by the issue of the appointment of a Lithuanian representative in Bonn (Lozoraitis and the VLIK appointed their own representative without any prior consultations). Lithuanian émigré legal experts, who have researched the legal status of the head of the Lithuanian diplomatic service and the VLIK, and the disagreements between them, have concluded that the aim of the institution of the Lithuanian diplomat was to foster the unity and the constitution of Lithuanian diplomacy abroad.From a legal point of view, the head of the diplomatic service and the VLIK were different organs: envoys were government appointees, while the VLIK was a public body. Efforts to provide a legal basis for the relations between Lozoraitis and the VLIK in the media and among experts did not have much influence on the relationship, though both sides sometimes resorted to them as a means to give more weight to their own arguments.
Keywords: emigree; emigree organizations; diplomacy; VLIK; S. Lozoraitis; Lithuanian Liberation Movement